2019
DOI: 10.1016/j.msksp.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular morphometric characteristics in low back pain with unilateral radiculopathy caused by disc herniation: An ultrasound imaging evaluation

Abstract: Background:Little is known about the neuromuscular morphometric characteristics in patients with sciatica.Objective: To evaluate the possible changes of nerve and muscle structures in patients with low back pain with unilateral radiculopathy due to lumbar disc herniation by ultrasound imaging. Design:A case-control observational study.Methods: Forty individuals were divided into case (n=20; low back pain with unilateral radiculopathy due to disc herniation), and healthy control groups (n=20). The thickness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…Ultrasound has been proven to be beneficial for evaluating nerves in humans (18)(19)(20)(21). The main pathological feature that has been demonstrated by MRI or ultrasonography is nerve enlargement (19,22), and several studies in human patients with sciatica have shown that the sciatic nerve is enlarged on the side of the sciatica (23,24). In dogs, diagnostic ultrasound has been used to locate nerves to perform nerve blocks (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been proven to be beneficial for evaluating nerves in humans (18)(19)(20)(21). The main pathological feature that has been demonstrated by MRI or ultrasonography is nerve enlargement (19,22), and several studies in human patients with sciatica have shown that the sciatic nerve is enlarged on the side of the sciatica (23,24). In dogs, diagnostic ultrasound has been used to locate nerves to perform nerve blocks (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Referente a la correlación encontrada entre la discopatía y la radiculopatía que se presentó en al menos el 98% de los casos, cabe señalar que es una incidencia más alta que lo que se ha mostrado en otros estudios, donde dicha correlación se reporta alrededor del 80%. Al parecer dicha correlación se asocia directamente con el mecanismo de deformidad de las discopatías y el efecto que estas generan directamente en las raíces nerviosas derivando en la radiculopatía 12,13 .…”
Section: Discussionunclassified
“…Patients were lying in either a comfortable supine or prone position, depending on the region of interest. NMU assessment of the patients followed a pre‐specified protocol with measurements performed at predetermined anatomical landmarks based on previously reported studies and existing literature 13–17 . The anatomical landmarks for NMU evaluations are depicted in Supplemental Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…NMU assessment of the patients followed a pre-specified protocol with measurements performed at predetermined anatomical landmarks based on previously reported studies and existing literature. [13][14][15][16][17] The anatomical landmarks for NMU evaluations are depicted in Supplemental Figure 1. The following parameters for each patient were recorded on both sides: CSA of the sciatic nerve and femoral nerves, fasciculation detection, and CSA measurements of prespecified muscles (see Supplemental Figure 1).…”
Section: Neuromuscular Ultrasound Evaluationmentioning
confidence: 99%